Krawiec wśród literackich wykrojów i wzorów - Wilk-Krzyżowska, Emilia (Tematy i Konteksty, 2018)
Publication of Prose: shapes and patterns depicts the author Jerzy Jarzębski as a tailor, showing literary shapes and patterns (forms) of works, thus creating his own literary map of Polish literature in the 20th and 21st century. Jarzębski focuses on the world of values, problems with the past, most popular topics and interviews, the aim of which is to depict the reader that there is no one ideal canon of literature. Each of us can create it ourselves, which the author encourages.